Estudo da contaminação da subsuperfície por hidrocarbonetos monoaromáticos nos principais postos de combustíveis das cidades de Bragança, Tracuateua e Augusto Corrêa (Pará) - CARMO, Raerida da Silva do (2024)
BTEX monoaromatic hydrocarbons (Benzene, Toluene, Ethylbenzene and Xylene) are petroleum products, soluble in water, highly volatile and highly dangerous for human health and the environment. The immediate detection of leaks is essential for the remediation of the contaminated area, since exposure to these compounds can cause irreversible problems for the environment, since they have a high impact on the soil, air and water and, consequently, attack various forms of life. . Leaks from gas stations contaminate groundwater, causing a series of environmental problems. Studies prove that human exposure to these compounds in high concentrations can cause a number of problems such as kidney failure, nervous system degradation, cancer and death. Before the detections of small concentrations of BTEX reported in previous research in the city of Bragança, in the present study the state of contamination by BTEX in this city as well as in the neighboring cities of Tracuateua and Augusto Corrêa was analyzed, applying the combination of analytical techniques Gas Chromatography (GC) and Mass Spectrometry (MS). Water samples were collected from nearby artesian wells and inside the main gas stations in these cities, during the rainy and dry seasonal periods in the 2021-2023 triennium. In each campaign (05 in total) 29 groundwater samples were collected (total of 145 samples), with 14 water samples collected in the city of Bragança, 03 samples in the city of Tracuateua and 12 in the city of Augusto Corrêa. 15 contaminated samples (11.72%) were detected in the cities of Bragança and Augusto Corrêa with toluene, ethylbenzene and xylene. Toluene and xylene were the most predominant contaminants. The values of the measured contaminants were within the maximum values allowed by current legislation. The remainder of the samples (88.28%) presented values below the Limit of Quantification of the combined GC-MS analytical techniques. These results add important information for public health, with the aim of alerting the competent bodies to start a process of environmental awareness with prevention and care measures before the existence of a possible contamination of the subsurface where the water table is being compromised in the places of the three cities studied, putting the potability of water for human consumption and the health of the population at risk.